Challenges to the role of the executive mayor in financial management at selected local municipalities in the Free State / Brutus Tshepo Mahlaku. - Mahlaku, Brutus Tshepo (North West University, 2015)
Local government, as government at grassroot, has, probably undergone transformation more than any institution in post-1994 South Africa. State-of the-art legislation have been passed that have restructured municipalities, and, especially, in the areas of performance and conduct of councillors and officials. Prominent in the areas of transformation are the roles of the Executive Mayor, which are no longer ceremonial as well as the radical changes which have been legislated in municipal financial management. This study was undertaken to determine the challenges that confront the Executive Mayor in financial management in selected local municipalities in the Free State. The hypothesis was formulated that "despite the state-of-the art legislation to regulate municipal finance, Executive Mayors in municipalities face the challenge of poor service delivery as a result of noncompliance to financial statutes due to human resource incapacity". To test the hypothesis, use was made by empirical research that comprised questionnaires completed by sample of managers and officials in the selected local municipalities of Mafube, Metsimaholo, Moqhaka and Ngwathe.The findings, amongst others, were that: • Human capital in the 4 selected local municipalities are in their prime age. 69 percent of managers are in the aged between 30 years to 50 years; • 57 percent of the managers responded that they have adequate qualifications and training to pursue the challenges in municipal finance; • All 4 municipalities normally get their budgets approved as required by compliance. • The hypothesis was consequently, invalidated. The study ends with recommendations to help improve standards and quality of financial management practice in the 4 municipalities.